2009
DOI: 10.1590/s0101-28002009000300002
|View full text |Cite
|
Sign up to set email alerts
|

Efeito de uma sessão de hemodiálise sobre o estresse oxidativo sistêmico de pacientes renais crônicos terminais

Abstract: Objective: To assess the effect of a hemodialysis (HD) session on systemic oxidative stress of chronic renal patients. Methods and Results: The study comprised 17 patients (10 women and 7 men with mean age of 39.9 ± 13.5 years) undergoing hemodialytic treatment at the Unit of Nephrology of Hospital de Clínicas de Porto Alegre, and a control group formed by 18 healthy individuals (4 women and 14 men with mean age of 34.8 ± 10.1 years). Renal patients had blood samples withdrawn before and after HD session. Mean… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
3
0
8

Year Published

2015
2015
2020
2020

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(12 citation statements)
references
References 33 publications
1
3
0
8
Order By: Relevance
“…This is probably the first evidence that the increase in this toxin during the uremic condition coincides with increased oxidative stress and neutrophil dysfunction in dogs. In uremic dogs, the increase in lipid peroxidation, estimated by plasma TBARS, associated with a decrease in plasma antioxidants (uric acid, albumin, and TAC) confirm that during uremia oxidative stress occurs, as has been described in humans , cats , and dogs .…”
Section: Discussionsupporting
confidence: 77%
“…This is probably the first evidence that the increase in this toxin during the uremic condition coincides with increased oxidative stress and neutrophil dysfunction in dogs. In uremic dogs, the increase in lipid peroxidation, estimated by plasma TBARS, associated with a decrease in plasma antioxidants (uric acid, albumin, and TAC) confirm that during uremia oxidative stress occurs, as has been described in humans , cats , and dogs .…”
Section: Discussionsupporting
confidence: 77%
“…The authors observed a decrease in serum total antioxidant capacity during the HD treatment, which was attributed to the dialytic removal of uric acid and ascorbic acid. Similarly, Bianchi et al [ 42 ] investigated the consequences of an HD session on the systemic oxidative stress of CKD patients, assaying serum samples with the total reactive antioxidant potential (TRAP) test; when pre- and post-HD sera of CKD patients were compared, it was observed a reduction in TRAP after one HD session.…”
Section: Discussionmentioning
confidence: 99%
“…Bianchi et al [ 42 ] assessed the oxidative damage of lipids in erythrocytes of CKD patients by chemiluminescence assays for LPO initiated by tert -butyl hydroperoxide (t-BOOH), which are sensitive and have been used to observe indirectly the previous oxidative stress and diminished endogenous antioxidants [ 55 , 56 ]. When chemiluminescence data from pre- and post-HD patients were compared, no differences were observed, but an increased chemiluminescence was observed when pre-HD patients were compared with healthy subjects, showing a state of oxidative stress in these patients.…”
Section: Discussionmentioning
confidence: 99%
“…Blood was collected by venipuncture in the cubital vein after local asepsis with 70% alcohol solution, with metal-free vacuum tubes containing EDTA as the anticoagulant (Vacuntainer ® , BD). A colorimetric method was used for Hb determination using Drabkin's reagent forming methemoglobin cyanide (Bianchi, Barp, Thomé, & Belló-Klein, 2009). Results are expressed as g/dl.…”
Section: Sample Collection Hb Blood Lead and Znpp Determinationsmentioning
confidence: 99%